Optical response of graphene under strain - Mousa, Amr (2022)
Strain has been known to modify the electric and optical properties of graphene. This phenomenon has attracted interest to modifying graphene properties using specific forms of strains (known as strain-engineering), and measuring strain in graphene. In this thesis, I present a calculation of the optical properties of strained graphene, where the effects of strain can be seen in the optical conductivity and thus the reflectivity of graphene.